A sub-stepping iterative constitutive model for cyclic cracking-crushing-shearing in masonry interface elements. (December 2021) - Xie, Z.; Sousamli, M.; Messali, F.; Rots, J.G.
Highlights: A constitutive model for interface elements is developed for use in masonry micromodelling. Model based on total deformation theory, considering failure in tension, compression and shear. Failure in tension and shear are coupled through a damage parameter. The sub-stepping algorithm (instead of mapping-back) ensures efficiency and robustness. Good agreement of hysteretic behavior and crack pattern between numerical and experimental results. Abstract: This paper proposes a sub-step based iterative constitutive model for line interface elements used to analyse masonry structures loaded in-plane. Based on a total deformation theory, the model adopts characteristics of multi-surface plasticity, including a Coulomb friction failure surface for shear, with tension and compression cut-off and softening for all three domains. The model is driven by two damage parameters, one for compression and one that couples tension and shear. The sub-stepping technique is demonstrated to be numerically stable and is used as an alternative to the traditional return-mapping algorithms, which are prone to convergence issues and instability. The proposed model has been validated against experimental tests performed on masonry walls subjected to cyclic, in-plane loading. The numerical simulations adequately identify the failure mode, the hysteretic behaviour and the crack pattern. When toe crushing is governing, the results appear to be sensitive to the assumed masonry compressive strength. It is shown that calibration of the lumped compressive strength makes possible to fully describe the damage evolution in walls that exhibit a mix of flexural crack-crush failure and shear failure. Overall, the model is demonstrated to be an efficient and robust tool for analysing the cyclic, in-plane behaviour of masonry walls.